CONSIDERATIONS ON TWO TYPES OF SOLID-STATE DOSIMETERS FOR IONIZING RADIATION - Ren, Tong (Wake Forest University, 2021)
Radiation therapy is a common type of treatment for cancer. Being able to measure the ionization radiation dose distribution with high resolution is of great importance for characterizing radiation devices and for quality assurance of patient radiation procedures. Two solid-state devices have been studied for their radiation dosimetric properties, to bring potential improvements for their use as dosimeters.\parFirst, radiochromic film is a robust two-dimensional dosimeter with high-resolution measurement capability. When digitized on a flatbed photo scanner, the fidelity of radiochromic film dosimetry is primarily affected by film active layer non-uniformity and the lateral artifact. At lower doses the low signal-to-noise ratio makes film active layer non-uniformity the primary source of error for accurate dosimetry. The error from the lateral artifact gradually increases with increasing dose. The first focus of this work is to develop a novel and efficient lateral artifact correction method as well as a channel weighted analytical method for film active layer non-uniformity correction. This channel weighted analytical approach accounts for the physical phenomenon that red, green and blue light with the same intensity are attenuated differently by the same attenuator. This phenomenon is characterized by the channel specific Napierian attenuation coefficient. For certain dose ranges and lateral positions on the scanner window, the new channel weighted analysis demonstrates better agreement with the plans calculated by the treatment planning system than the channel-independent analytical algorithm. The channel weighted approach does not require pre-irradiation film scans and is compatible with the existing, efficient one-scan protocol. The novel lateral artifact correction method is based on the one-scan protocol. The method utilizes fully exposed radiochromic film strips and corrects the lateral artifact in the dose domain of multichannel dosimetry. And it compensates for non-uniform off-axis output from open fields of a linear accelerator and the film active layer non-uniformity. This unique layout is symmetric about the scanner central-axis and covers the sufficient lateral space of a flatbed scanner. Radiation treatment plans validated with the new channel weighted and lateral artifact correction methods show improvements in passing rates when quantitatively analyzed using gamma criteria for the agreement of dose and distance parameters.\par Second, the metal-oxide-semiconductor field-effect transistor dosimeter can be used for in-vivo dose monitoring in external beam dosimetry for radiation therapy and radiosurgery. In this study, the response of an organic thin-film device to megavoltage X-rays is characterized. The device is based on organic field-effect transistor.